До проблеми законодавчого визначення сфери дії законодавства про працю, поняття та ознак трудових відносин - Венедіктов, В. С.; Venediktov, V. S.; Мельник, К. Ю.; Melnyk, K. Yu.; ORCID: http://orcid.org/0000-0002-8960-0234 (Право і безпека. - 2021. - № 1 (80). - С. 124-129, 2021)
Розглянуто норми проєкту Закону України «Про внесення змін до Кодексу законів про працю України щодо визначення поняття трудових відносин та ознак їх наявності» від 9 лютого 2021 р. № 5054. Досліджено погляди науковців стосовно сфери дії законодавства про працю, поняття та ознак трудових відносин. Визначено доцільність запровадження норм, пропонованих Проєктом до включення у Кодекс законів про працю України, стосовно сфери дії законодавства про працю, поняття та ознак трудових відносин. Сформульовано рекомендації щодо вирішення виявлених проблем.

The authors have studied the norms of the draft Law of Ukraine “On Amending the Labor Code of Ukraine to Define the Concept of Labor Relations and Features of Their Existence” dated from February 9, 2021 No. 5054. The scholars’ points of view on understanding the competence of labor legislation, concepts and features of labor relations have been studied. The authors have determined the expediency of introducing the norms suggested by the draft Law for inclusion in the Labor Code of Ukraine in relation to the competence of labor legislation, concepts and features of labor relations. Recommendations for solving the identified problems have been formulated. It has been offered to reflect the main features of labor relations in the concept of “labor relations” contained in Part 1 of the Art. 21 of the Labor Code of Ukraine provided by the draft Law, as well as to introduce a norm in the Art. 21-2 of the Labor Code of Ukraine of the following wording: “Work may be recognized as being performed within the employment relationship, if there are basic features of the employment relationship”. The main features of labor relations are as follows: 1) personal nature. Personal performance of work by an employee on a specific qualification, profession, position; 2) paid nature. Systematic payment of the salary for the performed works by an employer to an employee; 3) the nature of subordination to an employer. Work is performed by an employee on behalf of, under the guidance and control of an employer. The authors have suggested own definition of the term of “labor relations”, which is understood as a voluntary two-way communication between an employee and an employer, which involves personal performance of the work by an employee defined and paid by an employer under his guidance and control. The authors have developed own edition of the Art. 3 of the Labor Code of Ukraine; and have improved the provisions of the draft Law of Ukraine “On Amending the Labor Code of Ukraine to Define the Concept of Labor Relations and Features of Their Existence”.

Рассмотрены нормы проекта Закона Украины «О внесении изменений в Кодекс законов о труде Украины относительно определения понятия трудовых отношений и признаков их наличия» от 9 февраля 2021 г. № 5054. Исследованы точки зрения ученых относительно сферы действия законодательства о труде, понятия и признаков трудовых отношений. Определена целесообразность введения норм, предлагаемых Проектом к включению в Кодекс законов о труде Украины, относительно сферы действия законодательства о труде, понятия и признаков трудовых отношений. Сформулированы рекомендации по решению выявленных проблем.
К проблеме законодательного определения сферы действия законодательства о труде, понятия и признаков трудовых отношений
Regarding the problem of legislative definition of labor legislation’s competence, the concept and features of labor relations
Венедіктов, В. С. До проблеми законодавчого визначення сфери дії законодавства про працю, поняття та ознак трудових відносин / Валентин Семенович Венедіктов, Костянтин Юрійович Мельник // Право і безпека. - 2021. - № 1 (80). - С. 124-129. - DOI: 10.32631/pb.2021.1.17.
Венедіктов, В. С. і Мельник, К. Ю. (2021) «До проблеми законодавчого визначення сфери дії законодавства про працю, поняття та ознак трудових відносин», Право і безпека, 80(1), с. 124-129. doi: 10.32631/pb.2021.1.17.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; трудові відносини; трудовий договір; працівник; роботодавець; сфера дії; правоохоронні органи; трудовые отношения; трудовой договор; работник; работодатель; сфера действия; правоохранительные органы; labor relations; employment contract; employee; employer; competence; law enforcement agencies